Kajian Tentang Tarif Pelayanan Jasa Kargo dan Pos Pesawat Udara di Bandara Sam Ratulangi Manado - Dina Yuliana; Eny Yuliawati (WARTA ARDHIA, 2009)
Research about Cargo and Post Service Charge in Sam Ratulangi Airport has been done. The result show that Cargo and Post Service Charge based fare(Rp.515,- per kg) and cargo companys willingness to pay (Rp.323,- per kg) are higher than current cargo and post service charge (Rp.300,- per kg) and based on their perception it was proved that almost 53,3% stated good 46,7% fair and there is no client stated bad against the facility of Cargo and Post Service Charge outgoing domestic.